Export efficiency and determinants of Indonesian spices exports to major destination countries - Maya Aulia Ardini; Fahmi Salam Ahmad; Syarifah Amaliah (Universitas Ahmad Dahlan, 2026)
Indonesian spice exports (HS 0904 to 0910) have been a major contributor to non-oil and gas exports. One issue related to spice exports is that their performance often fluctuates and does not truly reflect the